Adapting English Teacher Professional Development to Shifting Educational Situations in Higher Education: Trends and Prospects - Gyawali, Yadu Prasad (Education and Development, 2022)
This study explores the need for transforming professional development for English teachers. Similarly, it focuses on the overview of traditional professional development methods and proposes alternative approaches, such as personalized learning and collaborative communities of practice. In addition, the article highlights the importance of aligning professional development with the evolving demands of the English language curriculum and the challenges posed by digital technologies. The study explores the necessity of adapting English teacher professional development programs to changing educational conditions through thematic-based content analysis of the research found in Google Scholar and Eric databases. Furthermore, related papers and litmaps were used to analyze the authorship and coverage of the study. Recent research from the ERIC and Google Scholar databases strengthens the need for ongoing, workplace-based, and personalized professional development programs that are connected with the evolving demands of the English language curriculum and digital technology. The findings of this study, thus, reinforce the need for transformative professional development programs that are aligned with the changing demands of the English curriculum and digital technology and prioritize the individualized learning needs of instructors. The research underlines the necessity for English teachers to adjust their professional development practices to meet the ever-evolving requirements imposed by the English curriculum. The results suggest that professional development strategies should be adapted to meet the changing educational circumstances. Overall, the study offers guidelines for the design and implementation of transformative professional development programs that improve teacher learning and student outcomes.